Environmental Activism in Russia: Changes in International Influence - Obydenkova, Anastassia (DEU, 2025)
This article analyzes changes in external influences on environmental activism in Russia. It identifies three main new trends - isolation from international environmental actors (e.g., Greenpeace, the World Wide Fund, and others) due to national persecution; the pausing of Russia's membership in international organizations (e.g., in the Arctic Council); and the emerging new international influence (e.g., from China and China-led international organizations). The article outlines the possible consequences and implications of these recent trends.